Cloning and Expression Profiling of the Polycomb Gene, Retinoblastoma-Related Protein from Tomato Solanum Lycopersicum L. (January 2014) - Almutairi, Zainab M.; Sadder, Monther T.
Cell cycle regulation mechanisms appear to be conserved throughout eukaryotic evolution. One of the important proteins involved in the regulation of cell cycle processes is retinoblastoma-related protein (RBR), which is a negative regulator of cell cycle progression, controlling the G1/S transition in plants and animals. In this study, we present the cloning and genomic structure of a putative SlRBR gene in the tomato Solanum lycopersicum L. by isolating cDNA clones that correspond to the SlRBR gene from tomato using primers that were designed from available Solanaceae ESTs based on conserved sequences between the PcG genes in Arabidopsis thaliana and tomato. The SlRBR cDNAs were cloned into the pBS plasmid and sequenced. Both 5′- and 3′-RACE were generated and sequenced. FlcDNA of the SlRBR gene of 3, 554 bp was composed of a 5′-UTR of 140 bp, an ORF of 3, 054 bp, and a 3′-UTR of 360 bp. The translated ORF encodes a polypeptide of 1, 018 amino acids. An alignment of the deduced amino acids indicates that there are highly conserved regions between the tomato SlRBR predicted protein and plant hypothetical RBR gene family members. Both of the unrooted phylogenetic trees, which were constructed using maximum parsimony and maximum likelihood methods, indicate a close relationship between the SlRBR predicted protein and the RBR protein of Nicotiana benthamiana . QRT-PCR indicates that SlRBR gene is expressed in closed floral bud tissues 1.7 times higher than in flower tissues, whereas the expression level in unripe fruit tissue is lower by about three times than in flower tissues.